The Influence Of Communication, Career Development, And Work Discipline On Employee Performance At The Two Medan Madya Tax Services Office - Dedy Agusman; Junior Ahmad Efendi; Zulham Efendi Ritonga; Paisal Amir Simatupang; Supar Wasesa; Zenni Riana (STIE Amkop Makassar, 2024)
This examination means to acquire demonstrated informative discoveries in regards to the impact of correspondence, profession advancement and work discipline somewhat and, at the same time, representative execution at the Medan Halfway Expense Administration Office. The speculation proposed is: There is a critical impact of correspondence, profession improvement and work discipline to some degree and mutually on representative execution at the Madya Dua Medan Expense Administration Office. The examination was led at the Madya Dua Medan Expense Administration Office Jalan Sukamulia No.17 A, North Sumatra DJP Local Place of Business I Floor 3, A U R, Medan Maimun Region, Medan City, North Sumatra Territory, postal code 20151, with a population of 117 individuals, and the exploration test included upwards of 54 individuals. In view of the consequences of the examination, it was found that correspondence meaningfully affected the exhibition of the Medan Two Halfway Expense Administration Office workers; this was upheld by the aftereffects of the t count < t-table 0.668 < 2.009 at n = 54 at an importance level of 95%. Vocation improvement affects the presentation of the Medan Two Moderate Expense Administration Office workers; this is upheld by the examination of t count > t-table (3.152 > 2.009) at n = 54 at an importance level of 95%. Work discipline affects the presentation of the Medan Two Halfway Expense Administration Office representatives; this is upheld by the investigation of t count < t-table (4.892 > 2.009) at n = 54 with an importance level of 95%. The worth of F-count > F table (29.979 > 2.79) expresses that together (various) there is a positive and huge impact of correspondence, vocation improvement and work discipline on the exhibition of representatives of the Medan Middle of the Road Duty Administration Office